Shrimp industry in China: overview of the trends in the production, imports and exports during the last two decades, challenges, and outlook - N’Souvi, Kodjo; Sun, Chen; Che, Bin; Vodounon, Anani (Frontiers in Sustainable Food Systems, 2024)
China’s shrimp farming industry has experienced significant growth in recent years. With such a development, some major constraints linked to the industry’s sustainable development have emerged. This paper aims to present an overview of China’s shrimp industry over the last two decades, with special attention to farm-raised shrimp both in marine and inland waters. Documentary research on its recent evolution was carried out based on data collected from China Fishery Statistics Yearbooks 2003 to 2022 coupled with data from FAO. Findings indicated that there has been an upward trend in China’s total shrimp production over the last 20 years, with a growth rate of 120%, representing an average annual growth rate of 4.3%. The observed higher shrimp production was driven by expanded shrimp aquaculture production, with major species dominated by the Pacific whiteleg shrimp (litopenaeus vannamei), the black tiger shrimp (Penaeus monodon), the Chinese shrimp (Penaeus chinensis), and the Japanese prawn (Penaeus japonicus). Challenges associated with the intensification of the production and the driven environmental deterioration need to be properly addressed. First, the shrimp farming industry should be practiced while considering both environment and ecosystem protection. Applying such an organic farming principle presupposes some practices for addressing the existing issues threatening the sustainable growth of the industry. To that end, there is a need for innovative techniques that should be strengthened. Second, possible solutions to shrimp disease problems, namely prevention, early diagnosis, and various control techniques, should also be developed and improved, with an emphasis on the former. In addition, encouraging the use of good-quality feed in appropriate quantity and form is also of paramount importance. It is thus worth noting that further policies need to focus on promoting a large range of ecological shrimp aquaculture technologies that should be encouraged among farmers.